Commodification Of Religion’s Value On Instagram Content-Study Case: Safi Indonesia - Rizqiani Dian Lestari; Ayu Sulistya Putri Sugeng; Fajar Harits (Jurnal Indonesia Sosial Teknologi, 2023)
As plenty of ‘religious values products’ have been sells and have a good market penetration, the writers consider to elaborate on how a brand bringing up the religious values to make their product accepted by market. Indonesia itself, have Islam religion as the majority. Therefore, the Islamic values tend to be accepted by market in Indonesia. This writing aimed to give an explanation and sample of how a brand tried to construct the market’s mind using Mosco’s theory about Economy Political and Communication through commodification, Spatialize and Structuration; featuring Semiotics analysis by Peirce’s, with Qualitative method by observing Safi Indonesia’s Instagram content. The writers use constructivism paradigm to observe how the brand build their market’s point of view towards a product with religious values. From the observation, the writers found that the symbol of religion have been used by the brand to construct market point of view, and accept the brand aiming a conversion to more sales